PENGARUH KUALIFIKASI GURU TERHADAP PENINGKATAN MUTU GURU AGAMA DI SEKOLAH DAN MADRASAH - Hayadin Hayadin (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This study aimed to determine the effect on the quality of teacher qualifi cations towards teachers qualities in the school and religious education in madrasas. These were include teachers’ pedagogical knowledge, the ability to make a lesson plan, the increasing of student test scores, and the teachers performance and creativity. This study was undertaken toward madrasas’ teacher qualifi cation improvement programs followers and religious education teacher at the school as well, through graduate school scholarship program. The data collecting techniques was using survey. The samples consisted of madrassa teacher and teacher of religion in the publicschools of alumni scholarships S2 and S1. The research instrument consisted of a questionnaire, and documents. The results showed that teacher qualifi cation have had infl uence on teachers’ pedagogical knowledge, the ability to create lesson plans, performance and teacher creativity and innovation.